Embolic Stroke Diagnosed by Elevated D-Dimer in a Patient With Negative TEE for Cardioembolic Source - Irina Y. Sazonova PhD; Roja Pondicherry-Harish MD; Nikhil Kadle BS; Gyanendra K. Sharma MD; Ramon E. Figueroa MD; Vincent J. B. Robinson MD (SAGE Publishing, 2014)
We report a case of cerebrovascular accident with thromboembolic stroke etiology in a patient who had atrial flutter and negative transesophageal echocardiography (TEE) results. The increased D-dimer levels (1877 ng/mL) initiated referral for magnetic resonance imaging and magnetic resonance angiography of the brain that showed classic recanalization of an embolic thrombus in the angular branch of the left middle cerebral distribution. The D-dimer level of this patient was normalized after 3 months of anticoagulation therapy. Although TEE is considered the gold standard for evaluation of cardiac source of embolism, exclusion of intracardiac thrombus with TEE alone does not eliminate the risk of thromboembolic events. This case highlights the utility of D-dimer as a potential adjunct in the decision-making process to guide investigation of thromboembolism, determine subsequent therapy, and hence reduce the risk of embolic stroke recurrence.